Allegories Of Underdevelopment : Aesthetics and Politics in Modern Brazilian Cinema - Xavier, Ismail (Book collections on Project MUSE., 1997)
Focusing on a variety of filmmaker's use of narrative allegories for the "conservative modernization" Brazil and other nations underwent in the 1960s and 1970s, Ismail Xavier examines the way Cinema Novo transformed Brazil's cultural memory. Includes discussions of Black God, White Devil, Land in Anguish, Red Light Bandit, Macunama, Antnio das Mortes, The Angel Is Born, and Killed the Family and Went to the Movies.